High-Dose Fluorescein Reveals Unusual Confocal Endomicroscope Imaging of Low-Grade Glioma - Belykh, Evgenii; Onaka, Naomi R.; Zhao, Xiaochun; Abramov, Irakliy; Eschbacher, Jennifer M.; Nakaji, Peter; Preul, Mark C. (Frontiers in Neurology, 2021)
Background: Fluorescence-guided brain tumor surgery using fluorescein sodium (FNa) for contrast is effective in high-grade gliomas. However, the effectiveness of this technique for visualizing noncontrast-enhancing and low-grade gliomas is unknown. This report is the first documented case of the concurrent use of wide-field fluorescence-guided surgery and confocal laser endomicroscopy (CLE) with high-dose FNa (40 mg/kg) for intraoperative visualization of tumor tissue cellularity in a nonenhancing glioma. Case Description: A patient underwent fluorescence-guided surgery for a left frontal lobe mass without contrast enhancement on magnetic resonance imaging. The patient received 40 mg/kg FNa intravenously at the induction of anesthesia. Surgery was performed under visualization with a Yellow 560 filter and white-light wide-field imaging. Intraoperative CLE produced high-quality images of the lesion 1.5 hours after FNa injection. Frozen-section analysis demonstrated findings comparable to those of intraoperative CLE visualization and consistent with World Health Organization (WHO) glioma grades II to III. The patient recovered without complications. Analysis of the permanent histologic sections identified the tumor as an anaplastic oligodendroglioma, IDH-mutant, 1p/19q co-deleted, consistent with WHO grade III because of discrete foci of hypercellularity and increased mitotic figures, but large regions of the lesion were low grade. Conclusions: The use of high-dose FNa in this patient with a nonenhancing borderline low-grade/high-grade glioma produced actionable wide-field fluorescence imaging using the operating microscope and improved CLE visualization of tumor cellularity. Higher doses of FNa for intraoperative CLE imaging and possible simultaneous wide-field fluorescence surgical guidance in nonenhancing gliomas merit further investigation.